2010
DOI: 10.2337/dc10-0255
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis Treatment Is an Independent Risk Factor for Foot Ulceration in Patients With Diabetes and Stage 4 or 5 Chronic Kidney Disease

Abstract: OBJECTIVETo determine whether dialysis treatment is an independent risk factor for foot ulceration in patients with diabetes and renal impairment.RESEARCH DESIGN AND METHODSWe performed a cross-sectional study of consecutive patients with diabetes and stage 4 or 5 chronic kidney disease (CKD) attending clinics in Manchester (U.K.). Patients were classified as either receiving dialysis therapy (dialysis) or not (no dialysis). Foot assessment included diabetic peripheral neuropathy (DPN), peripheral arterial dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
157
7
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(178 citation statements)
references
References 22 publications
12
157
7
2
Order By: Relevance
“…This could be true in the case of our study as all the subjects with LLA had concurrent DM which is strongly associated with foot ulceration. 12,25 On the other hand, the strong association between PAD and LLAs in the current study was reported by others 21 where calciphylaxis was thought to be a contributing factor. 15 Other risk factors for LLA identified in this study include peripheral neuropathy and retinopathy as previously reported.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…This could be true in the case of our study as all the subjects with LLA had concurrent DM which is strongly associated with foot ulceration. 12,25 On the other hand, the strong association between PAD and LLAs in the current study was reported by others 21 where calciphylaxis was thought to be a contributing factor. 15 Other risk factors for LLA identified in this study include peripheral neuropathy and retinopathy as previously reported.…”
Section: Discussioncontrasting
confidence: 42%
“…These studies have also identified that LLAs are a frequent event in patients on hemodialysis therapy (HD) and that this risk is further increased with the presence of concurrent DM. 12,15 Regarding the prevalence of LLAs in ESRF patients, on dialysis that has been recorded has a wide distribution from as low as 1.72% in Japan 16 to as high as 13.4% in Canada, 17 there is no recorded prevalence from the Australian continent even though Australian data suggests high rates of CVD, DM and ESRF amongst the indigenous population. 18,19 Indigenous Australians have been found to have a 38 times higher risk for LLA secondary to DM as compared to their non-indigenous counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And yet this review collates the overwhelming evidence from both cross-sectional and prospective studies, to indicate that the level of risk can be predicted, with the likelihood of new ulceration being variously increased by the presence of peripheral neuropathy, peripheral arterial disease, deformity and, in particular, by a history of previous ulceration or amputation. Other factors may be important, too, including visual impairment (with risk of foot trauma), renal dialysis (not referred to in this paper but known to be a powerful risk factor [3]) and HbA 1c . The role of the last of these may relate to its association with the development, or progression, of other complications of diabetes [4].…”
mentioning
confidence: 99%
“…Dialysis/ renal replacement therapy is strongly and independently associated with foot ulcers. [39][40][41][42] Neuropathy greatly increases the risk of pressurerelated ulcers, and care must be taken to ensure adequate pressure relief on patients' heels in renal dialysis units when they are recumbent for prolonged periods. 43 Podiatry input on dialysis units reduces the frequency and severity of diabetic foot complications: regular podiatry assessment (at least 3-monthly) should be ensured, ideally on dialysis units as this frail, multi-morbid population may have difficulty accessing community podiatry services.…”
Section: Section 6: Complications Of Diabetes In Haemodialysis Patientsmentioning
confidence: 99%